2017
DOI: 10.1111/maec.12429
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of diverse inter‐tidal algal assemblages in Southwest O‘ahu

Abstract: Spatial and temporal variation in tropical inter‐tidal communities is poorly known, making predictions about the effects of climate change and other anthropogenic disturbances difficult. Along Southwest O‘ahu, Hawai'i, local residents are concerned about the environmental effects of coastal development and the perceived loss of targeted algal species, which are collected for human consumption. To describe the coastal benthic community and better understand the processes that form and maintain it, the abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…“ A. amadelpha ” now inhabits the intertidal, subtidal, and mesophotic environments in Hawai‘i (Spalding 2012), and is considered invasive (Peyton 2009, Cox et al 2017), altering the benthic ecosystem (Martinez et al 2009), and competing with native species (Peyton 2009). Given these characteristics, considerable attention should be given to A. erecta in the Hawaiian Islands to monitor its possible expansion and competition with other psammophytic phototrophs in order to allow timely mitigation strategies if needed.…”
Section: Discussionmentioning
confidence: 99%
“…“ A. amadelpha ” now inhabits the intertidal, subtidal, and mesophotic environments in Hawai‘i (Spalding 2012), and is considered invasive (Peyton 2009, Cox et al 2017), altering the benthic ecosystem (Martinez et al 2009), and competing with native species (Peyton 2009). Given these characteristics, considerable attention should be given to A. erecta in the Hawaiian Islands to monitor its possible expansion and competition with other psammophytic phototrophs in order to allow timely mitigation strategies if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our model indicated that regions experiencing at least 5 DHW during 2013-2016 were more suitable for A. amadelpha invasion. Cox et al (2017) speculate that recent warming events in 2015 caused a die-back in abundant native intertidal macroalgae, facilitating the rapid spread of leather mudweed in this intertidal environment. They observed an opportunistic increase in abundance of A. amadelpha following the reduction in brown algae (Padina sanctae-crucis and Dictyota spp.…”
Section: Invasion Risk Under a Changing Climatementioning
confidence: 99%
“…They observed an opportunistic increase in abundance of A. amadelpha following the reduction in brown algae (Padina sanctae-crucis and Dictyota spp. ), which dominate multiple intertidal sites around Oahu (Cox et al, 2017). This invasion notably followed a period of unseasonably warm, calm seas and a series of severe bleaching events from 2014 to 2017.…”
Section: Invasion Risk Under a Changing Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Although described as the richest marine habitats (Costello & Chaudhary, ), tropical coastal areas are still under‐studied (Cox, Spalding, & Foster, ; Kaehler & Williams, ) when compared to temperate shores or coral reefs (e.g., Mieszkowska et al, ). We performed descriptive analyses of diversity in marine subtidal rocky reef communities in a tropical region (sensu Spalding et al, ) of Rio de Janeiro state, Brazil.…”
Section: Introductionmentioning
confidence: 99%